Ответ:
Объяснение:
1) a²+2ax+x²
2) y²-4y+4
3) 4a²+4a+1
4) 9c²-12c+4
5) 49-14a+a²
6) x⁴+2x²+1
7) a⁴+6a²x+9x²
8) c⁴+2c²d²+d⁴
9) a⁹+6a³b+9b²
11) a²-b²
12) 16a²-b²
13) 9x²-25y²
17) 3x²-6xy+3y²
18) 10a²-6ab+b²
19) 2a²+16
20) c²-4c
22) упростим выражение, получится 6a+13
6·(-3,5) +13 = -8
23) упростим выражение, получится 6x+9=0
6x=-9
x= -1,5
24) упростим выражение, получится -20x= -34
x=1,7
25) упростим выражение, получится 12x=5
x=5/12
26) упростим выражение, получится 10x=17
x=1,7
Answers & Comments